Validation of the Developed Innovative Supplemental Materials (ISMs) on the Least-learned Competencies in Grade 8 Physics - Paynandos, Jean Rose R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The main objective of this study is to validate the developed innovative supplemental materials (ISMs) as instructional support in mastering the least-learned competencies (LLC) in eighth-grade physics. The study underwent planning, development, and validation phases. Planning involved identifying the LLC and creating five ISMs. In the development stage, ISMs were built using Microsoft PowerPoint and iSpring Suite 11, incorporating PhET simulations and interactive videos accessible online and offline. Validation involved three experts and 60 students from three schools in the Tago II District. Statistical tools like weighted mean and ANOVA were used for data analysis. The findings revealed that experts rated the ISMs "very satisfactory" in content, instructional, technical quality, and supplementary evaluation. Posttest results of student-users showed positive mean gain scores greater than 7, indicating significant enhancement in learning outcomes. There was no significant difference in posttest results across the three schools (ρ = 0.584), underscoring the effectiveness of ISMs in enhancing LLC mastery in physics. Despite challenges such as intermittent connections, freezing slides, inoperative subtitles, sound synchronization issues, and malfunctioning control buttons, enhancements were made to address these problems. The study concludes that ISMs significantly improved students' mastery of LLC and recommends their use in teaching physics to make learning more effective and interactive as part of innovative pedagogical practices in education.